2018
DOI: 10.1016/j.fsigen.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA mixtures interpretation – A proof-of-concept multi-software comparison highlighting different probabilistic methods’ performances on challenging samples

Abstract: The present study investigated the capabilities and performances of semi-continuous and fully-continuous probabilistic approaches to DNA mixtures interpretation, particularly when dealing with Low-Template DNA mixtures. Five statistical interpretation software, such as Lab Retriever and LRmix Studio - involving semi-continuous algorithms - and DNA•VIEW, EuroForMix and STRmix- employing fully-continuous formulae - were employed to calculate likelihood ratio, comparing the prosecution and the defense hypotheses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…It has also been demonstrated that factors such as PCR and the content of allele frequency databases have an impact on the variation in the LR computed using a continuous method [ 28 , 29 ]. Recent work has demonstrated that differences in output between semi-continuous and continuous systems result in clear differences in the LRs for some samples [ 10 , 30 , 31 ]. Despite these studies, comparisons between continuous probabilistic systems are not readily available in the literature, though some examples using small datasets do exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that factors such as PCR and the content of allele frequency databases have an impact on the variation in the LR computed using a continuous method [ 28 , 29 ]. Recent work has demonstrated that differences in output between semi-continuous and continuous systems result in clear differences in the LRs for some samples [ 10 , 30 , 31 ]. Despite these studies, comparisons between continuous probabilistic systems are not readily available in the literature, though some examples using small datasets do exist.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Morimoto et al [ 31 ] compare the continuous system Kongoh to another continuous system, EuroForMix, and demonstrate that for most high-template simple mixtures tested the LR outcomes were similar; however differences in LRs obtained from each model were obtained for more complex mixtures wherein the authors attributed the variation in outputs as “differences in the computational principle of estimating peak height variances”. Though reports of inter-model comparisons in the scientific literature do exist, sometimes resulting in the use of multiple softwares to test one item of evidence [ 30 ], the published work use limited datasets or do not replicate the runs; thus, in this work, and pursuant to PCAST’s recommendation to publish large-scale studies, we supplement the forensic and scientific literary record by examining the variability between results obtained from four variants of CEESIt [ 32 ], a tool that computes a continuous LR for a person of interest. In addition to the LR, CEESIt computes the LR distribution by random sampling of genotypes conditioned on the defense’s hypothesis, as well as the so-called p- value for the LR, which is the proportion of LRs sampled that are at least as large as the LR for the person of interest.…”
Section: Introductionmentioning
confidence: 99%
“…(Bleka, Benschop, Storvik, & Gill, ) compared a qualitative versus quantitative mixture models, showing that the latter performs more efficiently because they take account of peak height information. (Alladio et al, ) compared three quantitative models (STRmix, EuroFormMix and DNAview) showing consistency of results, that is, different models built using different assumptions returned similar results when tested against the same data. Qualitative models, Lab Retriever and LRmix Studio, behaved consistently, but tended to give lower LRs compared to quantitative models. Different models/databases may be used to solve the same problem.…”
Section: The Dynamic Knowledge‐basementioning
confidence: 95%
“…3 and this is covered by separate validation studies reported elsewhere (e.g. [26,35,36]). Supplement D describes program checking carried out using R scripts that are available at the webpage www.euroformix/evaluations in a file named 'NumEval 2.1.0'.…”
Section: The Validation Status Of Csmentioning
confidence: 99%